2006
DOI: 10.1007/s11746-006-5016-z
|View full text |Cite
|
Sign up to set email alerts
|

Varietal and crop year effects on lipid composition of walnut (Juglans regia) genotypes

Abstract: The FA, unsaponifiable, and volatile constituents of oil from three walnut varieties from two consecutive crop years were studied. The walnut oils (WO) were rich in PUFA and low in saturated FA. The tocopherol fraction consisted mainly of γ-tocopherol. High contents of β-sitosterol were found, together with campesterol and ∆ 5 -avenasterol in similar amounts. Methylsterols present in WO were identified as cycloartenol, cyclolaudenol, cycloeucalenol, and 24-methylenecycloartanol. The hydrocarbon fraction was ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
86
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 21 publications
13
86
1
2
Order By: Relevance
“…Oil content ranged between 54.4 and 67.48%, and protein between 11.58 and 14.5% in 2009, (Table 1), whereas in 2010 these ranges were between 55.29 and 66.25% for oil, and between 11.99% and 14% for protein (Table 1). Protein content agreed with previous reports (Amaral et al, 2003;Savage et al, 1999), as well as fat content, although the lowest fat value was lower than any previous report (Crews et al, 2005;Amaral et al, 2003;Martinez et al, 2006;Bada et al, 2010). The significance of the year×genotype interaction (Table 2) indicated that oil content variability was significant between years for some genotypes, as a result of the specific response by these genotypes to the environmental conditions of the year.…”
Section: Oil and Protein Contentsupporting
confidence: 89%
See 2 more Smart Citations
“…Oil content ranged between 54.4 and 67.48%, and protein between 11.58 and 14.5% in 2009, (Table 1), whereas in 2010 these ranges were between 55.29 and 66.25% for oil, and between 11.99% and 14% for protein (Table 1). Protein content agreed with previous reports (Amaral et al, 2003;Savage et al, 1999), as well as fat content, although the lowest fat value was lower than any previous report (Crews et al, 2005;Amaral et al, 2003;Martinez et al, 2006;Bada et al, 2010). The significance of the year×genotype interaction (Table 2) indicated that oil content variability was significant between years for some genotypes, as a result of the specific response by these genotypes to the environmental conditions of the year.…”
Section: Oil and Protein Contentsupporting
confidence: 89%
“…Protein content was significantly different between years (Table 2), with a higher mean value in 2009 (Table 1). The effect of year was not significant for oil content (Table 2), although it had been significant in three other walnut cultivars (Martinez et al, 2006). Oil content ranged between 54.4 and 67.48%, and protein between 11.58 and 14.5% in 2009, (Table 1), whereas in 2010 these ranges were between 55.29 and 66.25% for oil, and between 11.99% and 14% for protein (Table 1).…”
Section: Oil and Protein Contentmentioning
confidence: 95%
See 1 more Smart Citation
“…Using rancimat test, fresh APSO showed a low oil stability index OSI (5.4 h) which, dramatically, decreased to 0.86 h at the end of the heating process. In fact, high levels of linoleic and linolenic acids may result in a lower oxidative stability and a shorter shelf life of the oils as declared by Martíneza et al (2006). Having a very low O/L ratio (0.4), APSO showed detectable trans isomerization level for palmitoleic, linoleic and eicosenoic acids before and after applying the heat treatment.…”
Section: Resultsmentioning
confidence: 98%
“…The PUFA/MUFA ratio varied from 1.54 to 3.97. Martinez et al (2006) reported that the PUFA/MUFA ratio changed from 2.22 to 4.54 in the walnut cultivars Franquette, Chandler and Criolla. In the current study, some walnut genotypes and cultivars contained higher amounts of oleic acid, linoleic acid, palmitic acid and linolenic acid than some other walnut genotypes.…”
Section: Resultsmentioning
confidence: 99%